A straightforward green synthesis of N-(tert-butylsulfinyl)imines. Issue 10 (25th November 2016) - Lv, Xirui; Zhou, Yue; Zhang, Anguo; Zhou, Lihong; Zeng, Qingle
Abstract : A straightforward and environment-friendly protocol for the synthesis of valuable chiral N -( tert -butylsulfinyl)imines has been developed. Different from traditional process with benzaldehydes as substrates, arylmethyl alcohols, benzylthiol, dibenzyl ether, thioether, and disulfide are used as alternative substrates to react with tert -butanesulfinamide in the presence of KO t Bu under air for the synthesis of chiral N -( tert -butylsulfinyl)imines. This is a transition metal-free, mild, cost-effective, and simple process.